Fuzzy-Prešić-Ćirić Operators and Applications to Certain Nonlinear Differential Equations. Issue 6 (1st November 2016) - Shukla, Satish; Gopal, Dhananjay; Rodríguez-López, Rosana
Abstract: In this paper, we introduce a new class of operators called fuzzy-Prešić-Ćirić operators. For this type of operators, the existence and uniqueness of fixed point in M-complete fuzzy metric spaces endowed with H -type t -norms are established. The results proved here generalize and extend some comparable results in the existing literature. An example is included which illustrates the main result of this paper. Moreover, some applications of our main theorem to the study of certain types of nonlinear differential equations are provided.